Analysis of District Government Governance in Busang Post the Bre-X Gold Mine Scandal Using the McKinsey 7S Framework - Muhammad Satya Satria; Alda Ramadani (International Journal Labs, 2026)
The Bre-X gold mining scandal (1993–1997) represents one of the most catastrophic failures of natural resource governance in modern history, resulting in investor losses exceeding US4.5 billion (approximately Rp147 trillion in current value) and exposing systemic institutional deficiencies within Indonesia's mining regulatory framework during the late Orde Baru (New Order) era. This study analyzes Busang District government governance using the McKinsey 7S Framework (Strategy, Structure, Systems, Shared Values, Skills, Style, and Staff). Through documentary analysis of government records, parliamentary investigations, and academic literature, the research identifies institutional misalignments that enabled four years of undetected fraud despite multiple oversight agencies. Key findings reveal strategic prioritization of revenue generation over regulatory compliance, structural fragmentation dispersing accountability across national, provincial, and district levels, systemic absence of independent assay verification and monitoring protocols, cultural normalization of patronage-based decision-making, technical skill deficiencies preventing fraud detection, leadership responsiveness to political pressure rather than technical judgment, and inadequate human resource development for mining oversight. These compounded failures created an environment of